The common and speci fic components of inflation expectation across European countries - Shi Chen; Wolfgang Karl Härdle; Weining Wang (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2020)
Inflation expectation (IE) is often considered to be an important determinant of actual inflation in modern economic theory, we are interested in investigating the main risk factors that determine its dynamics. We fiirst apply a joint arbitrage-free term structure model across different European countries to obtain estimate for country-specific IE. Then we use the two-component and three-component models to capture the main risk factors. We discover that the extracted common trend for IE is an important driver for each country of interest. Moreover a spatial-temporal copula model is tted to account for the non-Gaussian dependency across countries. This paper aims to extract informative estimates for IE and provide good implications for monetary policies.
Keywords: C02; C13; C38; E31; E43; 330; in ation expectation; joint yield-curve modeling; factor model; common trend; spatial-temporal copulas